INOVASI METODE PEMBELAJARAN SEKOLAH DASAR BERBASIS CONNECTION SEBAGAI PENGEMBANGAN KARAKTER SOCIAL ENTREPRENEURSHIP DALAM MEWUJUDKAN INDONESIA EMAS 2045 - Nugraha, Safana Arti Sabira; Amiludin, Amiludin (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Indonesia is predicted to enter the demographic bonus phase in 2045, this momentum is a golden opportunity as well as a big challenge in realising the Golden Indonesia 2045 so it needs to be prepared as much as possible. Literature study was used as the main method to collect data relevant to the research topic. This research highlights the urgency and strategy of designing Connection Based Learning at the primary school level and its implementation for Social Entrepreneurship character building. The results show that through this approach, learners can be developed into individuals who not only excel academically, but also have the critical thinking, creative, and social empathy skills needed in social entrepreneurship. Social-humanist 21st century learning in primary schools or madrasah ibtidaiyah through the Connection Based Learning approach is seen as an effective solution to prepare future generations who have social maturity and concern for humans and the environment. Primary school learning innovation based on the Connection approach can be a strategic solution to stimulate the growth of Social Entrepreneurship character from an early age which is also another alternative in Indonesia's social and economic development towards the Golden Indonesia 2045.